2013
DOI: 10.1016/j.watres.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of cesium from aqueous solution using agricultural residue – Walnut shell: Equilibrium, kinetic and thermodynamic modeling studies

Abstract: 15A novel biosorbent derived from agricultural residue -walnut shell (WS) is reported to remove cesium from aqueous 16 solution. Nickel hexacyanoferrate (NiHCF) was incorporated into this biosorbent, serving as a high selectivity trap 17 agent for cesium. Field emission scanning electron microscope (FE-SEM) and thermogravimetric and differential 18 thermal analysis (TG-DTA) were utilized for the evaluation of the developed biosorbent. Determination of kinetic 19 parameters for adsorption was carried out using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(101 citation statements)
references
References 31 publications
6
91
0
4
Order By: Relevance
“…Biochars are known to have the ability to adsorb organic and inorganic compounds, including heavy metals, and have been used for remediation of polluted soil (Beesley et al, 2011;Dias et al, 2007;Uchimiya et al, 2012). Adsorption of cesium by agricultural residues (coir pith and walnut shell), which were modified by incorporating nickel hexaxyanoferrate, was reported recently (Parab and Sudersanan, 2010;Ding et al, 2013), but to the best of our knowledge, cesium adsorption by biochar made of broiler litter has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Biochars are known to have the ability to adsorb organic and inorganic compounds, including heavy metals, and have been used for remediation of polluted soil (Beesley et al, 2011;Dias et al, 2007;Uchimiya et al, 2012). Adsorption of cesium by agricultural residues (coir pith and walnut shell), which were modified by incorporating nickel hexaxyanoferrate, was reported recently (Parab and Sudersanan, 2010;Ding et al, 2013), but to the best of our knowledge, cesium adsorption by biochar made of broiler litter has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…The Gibbs free energy change is related to the enthalpy (∆Hº) and the entropy (∆Sº) at any temperature using The values of ∆Hº (kJ/mol) and ∆Sº (kJ/mol.K) were calculated by plotting of ln Kd against 1/T [30, [54][55][56][57]. Table 6 Since, more of Mn 2+ ions replace the zeolites cations leads to more randomness in the system.…”
Section: Temperature Of Solutionmentioning
confidence: 99%
“…From Freundlich isotherm, the worth of 1/n, the Freundlich limit, that was between 0-1 additionally confirmed that the sorption was favorable and useful as low price sorbent [24,[41][42][43].…”
Section: Isothermal Analysismentioning
confidence: 89%
“…There is variety of natural adsorbents such clay [17], granular kohlrabi peel [18], peel [19], rice husk [20], raw barley straw [21], peanut husk [22], crab shell [23], and walnut shell [24]. Walnut shells are considered agricultural wastes with sensible chemical stability, high mechanical strength, simple regeneration and huge specific area.…”
Section: Introductionmentioning
confidence: 99%